Microsoft Dynamics 365 enterprise edition - financial management : maximize your business productivity through modern financial management in Dynamics 365 - Aamer, Mohamed (Packt Publishing, 2018)
Microsoft Dynamics 365 for finance and operations is a rapidly growing application and is widely used in enterprise organizations. Because of its ability to maximize business productivity, it is a fast-growing business application package in the ERP market. We will start by looking into ERP concepts, implementation needs, and interface design, giving you basic knowledge of financial management aspects and explaining key concepts along the way. To begin with, you'll be taken through the general ledger and financial dimension functions. You'll later learn about the sales tax mechanism and multi-currency in Microsoft Dynamics 365. We tackle each topic with focused examples and explanations on topics such as payable/receivable accounts, forecasting, cash and bank management, budgeting planning/control, and fixed assets. Finally, we walk you through intercompany, consolidation, costing basics, and financial reporting. By the end of this book, your finance team will have a much richer understanding of Microsoft Dynamics 365 for finance and operations and its powerful capabilities.